Fabrication of Transparent Superhydrophobic Surface and lts Anti-Frosting Performance - Fan Pengyan; Liu Zhongliang; Li Yanxia (Zhileng xuebao)
A method for preparing transparent superhydrophobic surfaces was proposed, and its anti-frosting performance at cold surface temperatures -3–5℃ and relative humidity 20%–60% was investigated. The experimental results show that the maximum contact angle of the transparent superhydrophobic glass surface prepared using silicon dioxide and polydimethylsiloxane is as large as 154.1° and has very good transparency. Frosting tests under vertical natural convection conditions indicated that the modified glass surface had a good anti-frosting effect. The frost layer formed consisted of a wheat-like spike structure in the early stage and transformed into an irregular bifurcation structure in the later stage, which is different from that of the unmodified glass surface whose frost layer structure consisted of flower clusters in the early stage and hexagonal frost crystals in the later stage. The contact angle of the modified glass surface first increased and then decreased with the nano-SiO2 coating amount, that is, there exists an optimum nano-SiO2 coating amount, found to be 0.067 g/cm2 under the experimental conditions covered. This optimum surface can remain unfrosted for 700 s, which is 66.7% longer than that of an unmodified glass surface. The results also revealed that the higher the relative humidity, the more obvious the dendritic growth of the frost crystal. The directional characteristics of frost crystal growth on the transparent superhydrophobic surface became more obvious as the humidity increased.